2011
DOI: 10.1016/j.yebeh.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Brain damage and IQ in unilateral Sturge–Weber syndrome: Support for a “fresh start” hypothesis

Abstract: We tested the hypothesis that extent of severe hypometabolism measured by glucose PET has a U-shaped (non-linear) relationship to IQ in children with unilateral Sturge-Weber Syndrome. Thirty-five consecutive children (age range, 30 to 153 months) with SWS and unilateral brain involvement were enrolled in the study. Participants underwent cognitive assessment and interictal glucose PET scans. Regression analyses tested whether a quadratic model best accounted for the relationship between extent of severe cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 19 publications
8
30
1
Order By: Relevance
“…14 As the leptomeningeal involvement and underlying brain damage is limited to one hemisphere in 85% of the cases, SWS is an excellent clinical model for studying reorganization of the brain, including the CST, after an early (often ongoing) postnatal unilateral brain injury. 15,16 In this study, we hypothesized differential changes in the CST segments associated with hand vs. leg motor control, and also looked for patterns of structural reorganization and their relation to clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…14 As the leptomeningeal involvement and underlying brain damage is limited to one hemisphere in 85% of the cases, SWS is an excellent clinical model for studying reorganization of the brain, including the CST, after an early (often ongoing) postnatal unilateral brain injury. 15,16 In this study, we hypothesized differential changes in the CST segments associated with hand vs. leg motor control, and also looked for patterns of structural reorganization and their relation to clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral brain involvement and early‐onset, frequent seizures are major predictors of poor clinical outcome 6, 10, 11. However, studies in unilateral SWS (representing the majority of SWS cases) suggested effective compensatory mechanisms leading to relatively preserved neurocognitive functioning in a subgroup of patients with extensive damage, presumably due to early functional reorganization in the contralateral (unaffected) hemisphere 4, 5, 6. Contralateral changes have been also documented by FDG‐PET in the form of increased cortical metabolism, mostly affecting posterior regions including the visual cortex 12, 13, 14.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course and outcome of SWS is highly variable, ranging from no or minimal neurological signs to severe impairment with uncontrolled seizures, hemiparesis, visual field cut, and learning disability 3. Cross‐sectional and longitudinal neuroimaging studies showed that some children with SWS show good neurocognitive outcome despite extensive unilateral brain involvement, presumably due to early, effective functional reorganization in the contralateral (unaffected) hemisphere 4, 5, 6. In a recent study, using susceptibility‐weighted imaging (SWI), an MRI sequence uniquely sensitive to small veins in the brain,7 we have also demonstrated a modest postnatal expansion of deep medullary veins in the early clinical course of two children with SWS, and its possible protective effect against progressive cortical damage 8…”
Section: Introductionmentioning
confidence: 99%
“…Clinical seizure frequency was evaluated by parent interviews and medical charts, and a seizure frequency score was assigned to each patient based on clinical seizures occurring during the one year period prior to the imaging study (or since seizure onset, if seizures started less than one year before the study). The scoring system was slightly modified from a previous study on children with SWS (Behen et al, 2011), and the scores were determined as follows: 0=no seizure in the last 1 year; 1: 1–11 seizures per year; 2: 1–4 seizures per month; 3: >4 seizures per month. Similar scores were also determined at follow-up, i.e., 1 year after baseline or at the time of epilepsy surgery, if surgery was done within one year after the baseline studies (Table 1).…”
Section: Methodsmentioning
confidence: 99%